Post-Construction Support and Sustainability in Community-Managed Rural Water Supply - Bakalian, Alexander; Wakeman, Wendy (World Bank, Washington, DC, 2012)
Water projects in developing countries are inaugurated with great fanfare by the governments, lenders, and sponsors that make them possible; the projects' results, however, don't always receive the publicity of groundbreaking ceremonies. This study reports the findings of a multi-country research project intended to discover how such rural water supply (RWS) systems actually perform. Its emphasis was on how performance was affected by post-construction support (PCS) to communities after project completion. Information was collected from households, village water committees (VWCs), focus groups of residents, system operators, and key informants in rural communities in Bolivia, Ghana, and Peru. Approximately 10,000 individuals registered their opinions. The great majority of the systems were found to be performing well; the factors influencing their sustainability should help policy makers, investors, and managers around the globe who plan rural water systems.